The Incumbent’s Curse, Party Institutionalization, and Competitive Factionalism in the Candidacy for South Halmahera Election in 2020 - Solihin, Eko Bagus; Rettob, Krisna; Effendi, David (Jurnal Politik, 2022)
This article investigates the incumbent’s curse in the candidacy process in Indonesia by using Bahrain Kasuba’s failure in the running for re-election in South Halmahera in 2020 as its case study. This study diverges from the traditional scholarship on the incumbent curse, which focuses on the election stage. Instead, we focus on the candidacy stage. Candidacy processes and elections are two different political events. Both have differences in three things: their victory targets, mechanisms, and political processes. These three differences urge the study of the effect of incumbency on candidacy, an important aspect to analyze. This article uses the party institutionalization and competitive factionalism frameworks to analyze how both factors affect the incumbent’s candidacy. We employed a case study method by conducting in-depth interviews with Bahrain Kasuba’s winning team and their competitors and exploring secondary data from media coverage and relevant literature. The study’s findings indicate that Bahrain Kasuba’s failure in the candidacy was caused by institutional factors, namely the weakness of party institutionalization and factionalism. In this case, the weakness of party institutionalization is characterized by the absence of ideological ties between parties and cadres and the lack of the party’s solidity as an organization. Meanwhile, factionalism occurred within parties and the Kasuba family, a dominant political elite in North Maluku. The factionalism in these two arenas placed Bahrain Kasuba in conflict with political party elites, which dictate the outcomes of candidacies.